The Influence of Leadership and Work Environment on Performance of the Production Team of a Timber Processing Company in Bojonegoro - Enoch David Lontolawa; Kustini Kustini (International Journal of Economics, Business and Innovation Research, 2025)
Entering the era of digitalization, companies are required to work efficiently and effectively, including the Wood Processing Company in Bojonegoro, a premium wood flooring export company based in Bojonegoro that was established in 1985. The company focuses on producing high-quality teak and merbau wood flooring to meet the market's need for aesthetic and durable products. However, in recent months, the company has faced a decline in production performance which is mainly influenced by human resource problems. This study aims to analyze the influence of leadership and work environment on the performance of the production team of a Timber Export Company.The research uses a saturated sampling method, where all members of the population are sampled. Thus, the research respondents were the entire production team of 44 people. Data was collected through questionnaires and analyzed using validity, reliability, and data processing tests with SmartPLS. The results of the study show that leadership has a significant positive influence on employee performance. In addition, the work environment has also been proven to have a positive and significant effect on employee performance.